Implementasi Pengacakan Bit Nilai Warna Spasi Pada Steganografi Di Dokumen Teks OOXML - Tri Yatmo Noveary; Kevin Ekaputra; Halim Agung (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Steganography exists due to the need to hide data in another data. The purpose of this research is to find another alternative in doing steganography via Office Open XML text document files. The research is done by library review, and application building. Design is done using flowcharts. Tests are done by comparing the result, and testing the endurance of the message via file format change, and content and name changing. From the result of the result, steganography done using space color code bit position randomization will not visually affect the document significantly. The message can endure conversions to file formats DOC, ODT, and PDF, 93% endure conversions to RTF file format, and cannot endure conversions to TXT file format, and can endure content change as long as there’s the sequence of files, and the spaces left intact.